Safe interaction between cyclists, pedestrians and automated vehicles. What do we know and what do we need to know? - (:unkn) unknown (My University, 2016)
Automated vehicles are gradually entering our roadway system. This report look into the position of pedestrians and cyclists in a future traffic system in which fully automated vehicles, partly automated vehicles and manually-driven vehicles have to share our roads. It provides an overview of current knowledge about the interaction of pedestrians and cyclists with (partly) automated vehicles. Furthermore, it identifies what we need to know in order to ensure that a (partly) automated driving system does not compromise the safety of pedestrians and cyclists.
Keywords: Individualverkehr; Fahrradverkehr; Infrastruktur; Untersuchung; Fußgängerverkehr; Fußgänger; Sicherheit; Verkehrssicherheit; Fahrzeug; Automatisierung; Verkehrstechnologie; Fahrradinfrastruktur; Radverkehrssicherheit; Studie